WVDM Living Lab: Sustainable renovation strategies for the VUB student residences of Willy Van Der Meeren. Issue 1 (1st December 2022) - Galle, W.; Elsen, S.; Wouters, I.; De Schepper, T.; Poppe, J.; De Temmerman, N.
Abstract: Like many institutions, Vrije Universiteit Brussel (VUB) strives for a sustainable approach to manage its architectural patrimony. This patrimony, with as an example the student residences in the heart of VUB its main campus, puts forward an important challenge. These residences, designed by architect Willy Van Der Meeren in 1971-1973, are generally recognized as architectural heritage, yet they need thorough yet economically feasible and future-oriented energy refurbishment if we want to extend their service life. The same challenge applies to many buildings in the Brussels Capital Region. Here, the number of housing units, as in the rest of Europe, increased significantly during the post-war period. A peak occurred at the end of the 1960s, when more than 7, 000 new housing units were built annually. Like the student residences, these housing units are the witnesses of an innovative past but raise questions on thermal inertia, safety of accessible roofs, performance of aluminium window frames, façades containing asbestos, etc. Unfortunately, today's practice shows that there is restricted time and resources to develop and compare alternative renovation strategies, lowering the ambitions in terms of heritage, energy, sustainability, and affordability. Therefore, in the WVDM Living Lab we took the opportunity to have researchers and project managers joining forces with practitioners. This project, that fits the Test-It program by Innoviris and is funded by EFRO and the Brussels Capital Region, with complementary investments from the infrastructure and patrimony office of VUB, provided oxygen to break through this lock-in. Using the student residences as a testbed for the development of sustainable renovation strategies for the former student residences and similar post-war heritage of Brussels, innovation in construction and in cooperation was found. First, the different consortia of designers, contractors and experts effectively developed and prototyped new design and construction solutions. Their proposals aligned heritage and sustainable material management in the idea of a circular economy and included for example the adoption of reversible connections and reused materials. Second, the consortia indicated that their mission to innovate also challenged their own organization and design process. Inspired by this experience, client and design team are convinced that working more closely together from the start of a construction project is crucial to reach innovative sustainable construction.